Obstructive Sleep Apnea With Objective Daytime Sleepiness Is Associated With Hypertension - Ren, Rong; Li, Yun; Zhang, Jihui; Zhou, Junying; Sun, Yuanfeng; Tan, Lu; Li, Taomei; Wing, Yun-Kwok; Tang, Xiangdong (Hypertension (Dallas, Tex. 1979), 2016)
Subjective daytime sleepiness is considered a significant risk factor of hypertension in patients with obstructive sleep apnea (OSA). In this study, our goal was to examine the joint effect on hypertension of OSA and objective daytime sleepiness measured by the multiple sleep latency test (MSLT). A total of 1338 Chinese patients with OSA and 484 primary snorers were included in the study. All subjects underwent 1 night polysomnography followed by MSLT. The MSLT values were classified into 3 categories: >8 minutes, 5 to 8 minutes, and <5 minutes. Hypertension was defined based either on direct blood pressure measures or on diagnosis by a physician. After controlling for confounders, OSA combined with MSLT of 5 to 8 minutes increased the odds of hypertension by 95% (odds ratio, 1.95; 95% confidence interval, 1.10-3.46), whereas OSA combined with MSLT <5 minutes further increased the odds of hypertension by 111% (odds ratio, 2.11; 95% confidence interval, 1.22-3.31) compared with primary snorers with MSLT >8 minutes. In stratified analyses, the association of hypertension with MSLT in OSA patients was seen among both sexes, younger ages, both obese and nonobese patients, and patients with and without subjective excessive daytime sleepiness. We conclude that objective daytime sleepiness is associated with hypertension in patients with OSA.